2019
DOI: 10.1097/md.0000000000014542
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic interventions for postoperative nausea and vomiting after thyroidectomy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…PONV has always been a major concern for anesthesiologists, as it is known to occur in up to 60% to 84% of patients after thyroidectomy if prophylactic antiemetics are not administered. [ 25 ] Therefore, most of the studies on postoperative complications after thyroidectomy are based on anesthesia methods or related drugs to reduce PONV or postoperative pain. However, postoperative pain after thyroidectomy is known to be mild to moderate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PONV has always been a major concern for anesthesiologists, as it is known to occur in up to 60% to 84% of patients after thyroidectomy if prophylactic antiemetics are not administered. [ 25 ] Therefore, most of the studies on postoperative complications after thyroidectomy are based on anesthesia methods or related drugs to reduce PONV or postoperative pain. However, postoperative pain after thyroidectomy is known to be mild to moderate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 , 27 ] PONV can cause complications such as aspiration pneumonia, fluid and electrolyte imbalances, or esophageal rupture, increasing the length of the patient’s hospital stay and medical costs and reducing the patient’s satisfaction with the surgery. [ 25 , 28 ] In particular, if it occurs after thyroidectomy, it may cause bleeding in or rupture of the surgical site, leading to airway obstruction due to hematoma in severe cases. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed the protocol for this systematic review and NMA according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) protocol statement [ 22 ] and registered it with the International Registration of Prospective Systematic Reviews (PROSPERO network); registration number: CRD42018100002; accessible at ( https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=100002 ), and published in a peer-reviewed journal [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported that, if not treated, ~35% of patients will develop nausea, vomiting, or both symptoms after surgery, which is a very painful experience, even more serious than postoperative pain ( 6 ). However, ~60–80% of patients develop nausea and vomiting after thyroidectomy without antiemetic prophylaxis, which may result in severe complications, such as aspiration pneumonia caused by accidental inhalation of vomitus or postoperative neck hematoma and even airway obstruction caused by hematoma ( 7 ). PONV often prolongs the patient's stay in the recovery room or even the discharge time, which is the main reason for accidental readmission after elective surgery ( 8 ).…”
Section: Introductionmentioning
confidence: 99%